Disentangling the effects of terroir, season, and vintage on the grapevine fungal pathobiome - Leal, Carla Mota; Geiger, Adrienn; Molnár, Anna; Váczy, Kálmán Z.; Kgobe, Glodia; Zsófi, Zsolt; Geml, József (Frontiers in Microbiology, 2024)
The composition, diversity and dynamics of microbial communities associated with grapevines may be influenced by various environmental factors, including terroir, vintage, and season. Among these factors, terroir stands out as a unique possible determinant of the pathobiome, the community of plant-associated pathogens. This study employed high-throughput molecular techniques, including metabarcoding and network analysis, to investigate the compositional dynamics of grapevine fungal pathobiome across three microhabitats (soil, woody tissue, and bark) using the Furmint cultivar. Samples were collected during late winter and late summer in 2020 and 2021, across three distinct terroirs in Hungary’s Tokaj wine region. Of the 123 plant pathogenic genera found, Diplodia, Phaeomoniella, and Fusarium displayed the highest richness in bark, wood, and soil, respectively. Both richness and abundance exhibited significant disparities across microhabitats, with plant pathogenic fungi known to cause grapevine trunk diseases (GTDs) demonstrating highest richness and abundance in wood and bark samples, and non-GTD pathogens prevailed soil. Abundance and richness, however, followed distinct patterns Terroir accounted for a substantial portion of the variance in fungal community composition, ranging from 14.46% to 24.67%. Season and vintage also contributed to the variation, explaining 1.84% to 2.98% and 3.67% to 6.39% of the variance, respectively. Notably, significant compositional differences in fungi between healthy and diseased grapevines were only identified in wood and bark samples. Cooccurrence networks analysis, using both unweighted and weighted metrics, revealed intricate relationships among pathogenic fungal genera. This involved mostly positive associations, potentially suggesting synergism, and a few negative relationships, potentially suggesting antagonistic interactions. In essence, the observed differences among terroirs may stem from environmental filtering due to varied edaphic and mesoclimatic conditions. Temporal weather and vine management practices could explain seasonal and vintage fungal dynamics. This study provides insights into the compositional dynamics of grapevine fungal pathobiome across different microhabitats, terroirs, seasons, and health statuses. The findings emphasize the importance of considering network-based approaches in studying microbial communities and have implications for developing improved viticultural plant health strategies.